Assessing Mothers’ Parenting Stress: Differences Between One- and Two-Child Families in China - Qian, Guoying; Mei, Jin; Tian, Li; Dou, Gang (Frontiers in Psychology, 2021)
This study aimed to investigate mothers’ parenting stress and explore its relationship with associated demographic variables in two-child families involving preschool children. A sample of 621 two-child families and a comparison group of 319 one-child families from China participated in the study; the children were aged between 3 and 7. The results showed that (1) mothers of two-child families had higher parenting stress than those of one-child families; (2) within the two-child families, demographic variables, such as birth order, gender combination, and the age gap were found to have significant effects on maternal stress levels; and (3) in two-child families, families with an income of less than 3000 yuan had significantly higher maternal stress than families with an income of more than 6000 yuan.